2002
DOI: 10.1016/s0140-6736(02)11133-0
|View full text |Cite
|
Sign up to set email alerts
|

The world report on violence and health

Abstract: In 1996, the World Health Assembly declared violence a major public health issue. To follow up on this resolution, on Oct 3 this year, WHO released the first World Report on Violence and Health. The report analyses different types of violence including child abuse and neglect, youth violence, intimate partner violence, sexual violence, elder abuse, self-directed violence, and collective violence. For all these types of violence, the report explores the magnitude of the health and social effects, the risk and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

85
3,650
9
500

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 5,529 publications
(4,244 citation statements)
references
References 23 publications
85
3,650
9
500
Order By: Relevance
“…Most of the interviewees in the present study were educated, and only two were illiterate; some even had university education, although most worked as manual workers in Sweden, a finding that has also been reported by other researchers [26,51]. Previous research findings have shown that women who are empowered educationally, economically and socially are the most protected in situations of male intimate partner violence [19,20,46]. …”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Most of the interviewees in the present study were educated, and only two were illiterate; some even had university education, although most worked as manual workers in Sweden, a finding that has also been reported by other researchers [26,51]. Previous research findings have shown that women who are empowered educationally, economically and socially are the most protected in situations of male intimate partner violence [19,20,46]. …”
Section: Discussionsupporting
confidence: 83%
“…Violence against women has been identified as a major public health and human rights problem throughout the world [1921]. The World Health Organization (WHO) emphasises that violence by men towards women is a significant health problem affecting one in three women globally [19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The World Health Organization (WHO) has recognised interpersonal violence as an important, worldwide public health issue that adversely affects both mental and physical health [1]. Childhood violence is defined as all forms of physical and/or emotional maltreatment, sexual abuse, neglect, negligence and commercial or other exploitation, which result in actual or potential harm to the child`s health, survival, development or dignity in the context of a relationship of responsibility, trust or power[2].…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 20% of women and 5–10% of men report childhood sexual abuse. Nearly a quarter of adults (22.6%) suffered physical abuse as a child, and 36.3% suffered emotional abuse [1]. The lifelong consequences of child maltreatment include impaired physical and mental health, poorer school performance, and job and relationship difficulties [36].…”
Section: Introductionmentioning
confidence: 99%